OPTIMIZATION OF UTILIZING STATE-OWNED ASSETS BY THE CENTRAL GOVERNMENT UPON THE RELOCATION OF THE CAPITAL CITY TO INCREASE NON-TAX STATE REVENUE: A CASE STUDY OF STATE ASSET IN THE GOLDEN TRIANGLE AREA OF DKI JAKARTA - Radjendra, Rahmantoro
The relocation of the capital city from DKI Jakarta to East Kalimantan affects the use of state assets, including land and buildings used to fulfill the duties and functions of various ministries/agencies. State assets located in DKI Jakarta may become less useful due to their discontinuation in governmental activities, potentially leading to neglect and suboptimal utilization. This can burden the state budget (APBN) with maintenance obligations. This study examines a specific state asset located in the Golden Triangle area of DKI Jakarta. The approach taken is quantitative research. The aim of this study is to optimize a single state asset by identifying the highest and best use (HBU) of an asset that may become neglected. Furthermore, it aims to estimate the non-tax state revenue (PNBP) from the utilization of the state asset. Data collection for this study includes state asset (BMN) data and property market data. The analytical methods used are property valuation, highest and best use analysis, and economic benefit estimation. In this effort, the government is conducting HBU studies to determine the best utilization of these assets. This thesis aims to contribute to estimating the potential non-tax state revenue (PNBP) that can be generated from the utilization of state land and buildings after the capital relocation, specifically in the Golden Triangle area of DKI Jakarta. The analysis results indicate that the potential asset in the Golden Triangle is the Bappenas Tower, with the most feasible highest and best use being retail property. The forms of utilization of state assets that can be implemented include leasing, cooperation in utilization (KSP), and build-operate-transfer (BGS/BSG), generating non-tax state revenue ranging from 500 billion rupiahs to 1.8 trillion rupiahs over a 30-year utilization period.